Analgesic effects of indomethacin spray on drug‐induced oral mucositis pain in patients with cancer: A single‐arm cross‐sectional study. (18th March 2021) - Hata, Hironobu; Takada, Shinya; Sato, Jun; Yoshikawa, Kazuhito; Imamachi, Kenji; Edo, Minako; Sagawa, Tamotsu; Fujikawa, Koshi; Ueda, Michihiro; Matsuzaka, Masashi; Kitagawa, Yoshimasa
Abstract: Aims: Symptomatic treatment is insufficient for chemotherapy‐ or targeted therapy‐induced oral mucositis (OM) pain, and benzydamine mouthwash is not commercially available in Japan. We evaluated the analgesic effects of an in‐hospital preparation of 0.25% indomethacin spray (IMS) on anticancer drug‐induced OM pain. Methods: This single‐arm prospective trial enrolled 20 patients (median age 62.0 years) with OM and numerical rating scale scores of ≥5 who were undergoing chemotherapy or targeted therapy in our hospital. Pain scores were recorded using a visual analog scale (VAS) before and 30 min after IMS administration. Pain relief (PR) scores were recorded at 15, 30, and 60 min after IMS administration; total PR after 60 min (TOTPAR60 ) was calculated, and the mean PR score after 3 days (PR3days ) was determined. Results: The median (interquartile range) OM grade of the participants was 2.0 (2.0–2.3). The VAS score decreased significantly at 30 min after IMS administration ( p  = .001). The median (interquartile range) TOTPAR60 and PR3days were 6.0 (3.8–7.3) and 2.0 (2.0–3.0), respectively. Conclusions: IMS helped improve patients' quality of life. The risk of systemic adverse effects was low because of the low dose administered. IMS effectively relieved anticancer drug‐induced OM pain and may be useful for immediate self‐medication.